Correspondence of Florence O'Donoghue with Dan Bryan, Moss Twomey and others regarding Ireland and Germany in World War II, with notes and newsclippings of a series by J.P. Gallagher in 'Sunday People' and extracts from Enno Stephan’s 'Secret mission - Ireland' in 'Sunday Review' - Gallagher, Joseph P.; Bryan, Dan 1900–1985; Stephan, Enno; Twomey, Moss, 1896-1978; O'Donoghue, Florence, 1895-1967 (1961)
Also includes notes by O'Donoghue and others and article based on interviews of J.P. Gallagher with Stephen Hayes.
Keywords: Hayes, Stephen; World War, 1939-1945; Ireland -- History -- 20th century; Ireland -- Foreign relations -- 20th century; Germany -- Foreign relations -- 1933-1945